PERLINDUNGAN HUKUM TERHADAP KONSUMEN TERKAIT PRODUK KOSMETIK YANG MENYEBABKAN KETERGANTUNGAN DI BPOM PROVINSI BALI - Dyah Nanda Widyaswari, Ni Made; Ari Yuliartini Griadhi, Ni Made (Kertha Semaya : Journal Ilmu Hukum, 2015)
This scientific work titled Against Consumer Protection Law Related ProductsCosmetics which causes Addiction Drug and Food of Bali Province. The background ofthis paper is that species circulating in the community cosmetics that contain harmfulsubstances that cause dependence when used by consumers. The purpose of this paperis to understand the forms of legal protection against related consumer cosmeticproducts which cause dependence and legal sanctions for sellers manufacturers ofcosmetic products that contain hazardous substances that can cause dependence. Thispaper uses empirical methods. The conclusion of this paper is that consumers get thelegal protection of Act Nomor 8 of 1999 on Consumer Protection Article 19 andperpetrators of crimes against cosmetic products that cause dependence may be subjectto administrative sanctions, civil or criminal sanctions provided for in Article 60 of LawNomor 8 of 1999 on Consumer Protection for administrative sanctions, Article 62 ofLaw Nomor 8 of 1999 on Consumer Protection for criminal sanctions. as well as article1365 and article 1371 of the civil code for civil sanctions.
Keywords: Protection Law, Consumer and Cosmetic Products